The struggle over the soul of economics : institutionalist and neoclassical economists in America between the wars - Yonay, Yuval P., 1958- (Princeton, N.J. : Princeton University Press, 1998)
This book provides a surprising answer to two puzzling questions that relate to the very ""soul"" of the professional study of economics in the late twentieth century. How did the discipline of economics come to be dominated by an approach that is heavily dependent on mathematically derived models? And what happened to other approaches to the discipline that were considered to be scientifically viable less than fifty years ago? Between the two world wars there were two well-accepted schools of thought in economics: the ""neoclassical, "" which emerged in the last third of the nineteenth cent
Book Cover; Title; Copyright; Contents
Includes bibliographical references (pages 251-278) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Institutional economics -- History -- 20th century; Neoclassical school of economics -- History -- 20th century; Economics -- United States -- History -- 20th century; Institutionnalisme -- Histoire -- 20e siècle.; École néoclassique d'économie politique -- Histoire -- 20e siècle.; Économie politique -- États-Unis -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Economics -- Theory; Economics; Institutional economics; Neoclassical school of economics; United States; 1900-1999; History